2023
DOI: 10.1021/acs.orglett.3c00307
|View full text |Cite
|
Sign up to set email alerts
|

General Method for Selective Three-Component Carboacylation of Alkenes via Visible-Light Dual Photoredox/Nickel Catalysis

Abstract: A photoredox/nickel dual catalytic protocol for the regioselective three-component carboacylation of alkenes with tertiary and secondary alkyltrifluoroborates as well as acyl chlorides is described. This redox-neutral protocol can be applied to the rapid synthesis of ketones with high diversity and complexity via a radical relay process. Many functional groups, allowing for various commercially available acyl chlorides, alkyltrifluoroborates, and alkenes, are tolerated under these mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
(20 reference statements)
2
6
2
Order By: Relevance
“…Scope of Carboxylic Acids a a Reaction conditions: 1 (0.2 mmol, 1.0 equiv), 2a (1.5 equiv), DMDC (1.5 equiv), NiBr 2 •DME (10 mol %), L1 (12 mol %), 4CzIPN (2 mol %), THF (1 mL), 30 W blue-light irradiation (455 nm), r.t., 18 photocatalyst probably also affected the activity of the catalytic system. Different from the previous report regarding photoredox/Ni-catalyzed three-component carboacylation, 28 adding (1-cyclopropylvinyl)benzene only resulted in a slight decline in the yield of target product 3a (Scheme 5b), and 58% of (1cyclopropylvinyl)benzene was recovered after reaction. During the reaction, part of (1-cyclopropylvinyl)benzene was converted to an unidentifiable complex mixture.…”
contrasting
confidence: 84%
“…Scope of Carboxylic Acids a a Reaction conditions: 1 (0.2 mmol, 1.0 equiv), 2a (1.5 equiv), DMDC (1.5 equiv), NiBr 2 •DME (10 mol %), L1 (12 mol %), 4CzIPN (2 mol %), THF (1 mL), 30 W blue-light irradiation (455 nm), r.t., 18 photocatalyst probably also affected the activity of the catalytic system. Different from the previous report regarding photoredox/Ni-catalyzed three-component carboacylation, 28 adding (1-cyclopropylvinyl)benzene only resulted in a slight decline in the yield of target product 3a (Scheme 5b), and 58% of (1cyclopropylvinyl)benzene was recovered after reaction. During the reaction, part of (1-cyclopropylvinyl)benzene was converted to an unidentifiable complex mixture.…”
contrasting
confidence: 84%
“…In conclusion, we have demonstrated that the enantioselective 3-component carboesterification of 1,3-dienes can be achieved using a range of readily available potassium alkyltrifluoroborates as the carbon/alkyl radical source. 33 The reaction is solvent, oxidant, and ligand dependent where CH 2 Cl 2 or 1,2dichloroethane (DCE) are the best solvents, MnO 2 is the best oxidant, and the cyclopentyl bridged phenyl-bis(oxazoline) L2 as well as the Me/Bn bridged phenyl-bis(oxazoline) L7 are the best ligands thus far identified. The range of alkyltrifluoroborates that work in this reaction is most broad in DCE upon heating at 75 or 105 °C, and very good isolated yields of the allylic ester adducts can be obtained with modest to very good enantioselectivities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In 2023, Wang et al [63] reported photoredox/nickel dual catalytic synthetic methodology to achieve regioselective three-component carboacylation of alkenes with acyl chlorides and tertiary/secondary alkyltrifluoroborates to synthesize 50 d with a maximum yield of 91 % (Scheme 50). Ir[dF(CF 3 )ppy] 2 (bpy)(PF 6 ) served as the photocatalyst which helps to produce alkyl radical from alkyl fluoroborate.…”
Section: 2-dicarbofunctionalization Of Alkene Using Dual Catalysismentioning
confidence: 99%